Case Report: Life-Threatening Post-operative Hemorrhage in Klippel–Trenaunay Syndrome Associated With Hypofibrinogenemia - Yang, Hongna; Du, Binfeng; Liu, Han; Yao, Yong; Li, Chen (Frontiers in Medicine, 2021)
Klippel-Trenaunay Syndrome (KTS) is a rare congenital disorder, characterized by venous and lymphatic malformations of the skin, soft tissue, and bone causing limb hypertrophy. Although ruptured hemorrhagic corpus luteum is the rare condition in women of reproductive age, it can result in the lethal outcome. Here, we described a patient with KTS and hypofibrinogenemia, who went through recurrent lethal postoperative bleeding due to ruptured hemorrhagic corpus luteum. This case suggested that conservative therapy might the first choice and effective therapy for the patients with KTS, who suffered from bleeding complication of surgical therapy.